Diverse Roles of PUF Proteins in Germline Stem and Progenitor Cell Development in C. elegans - Wang, Xiaobo; Voronina, Ekaterina (Frontiers in Cell and Developmental Biology, 2020)
Stem cell development depends on post-transcriptional regulation mediated by RNA-binding proteins (RBPs) (Zhang et al., 1997;Forbes and Lehmann, 1998;Okano et al., 2005;Ratti et al., 2006;Kwon et al., 2013). Pumilio and FBF (PUF) family RBPs are highly conserved post-transcriptional regulators that are critical for stem cell maintenance (Wickens et al., 2002;Quenault et al., 2011). The RNA-binding domains of PUF proteins recognize a family of related sequence motifs in the target mRNAs, yet individual PUF proteins have clearly distinct biological functions (Lu et al., 2009;Wang et al., 2018). The C. elegans germline is a simple and powerful model system for analyzing regulation of stem cell development. Studies in C. elegans uncovered specific physiological roles for PUFs expressed in the germline stem cells ranging from control of proliferation and differentiation to regulation of the sperm/oocyte decision. Importantly, recent studies started to illuminate the mechanisms behind PUF functional divergence. This review summarizes the many roles of PUF-8, FBF-1, and FBF-2 in germline stem and progenitor cells and discusses the factors accounting for their distinct biological functions. PUF proteins are conserved in evolution, and insights into PUF-mediated regulation provided by the C. elegans model system are likely relevant for other organisms.